PERAN NOTARIS DAN KEABSAHAN AKTA RUPS YANG DILAKSANAKAN SECARA ELEKTRONIK - Merdi Aditya Putra; Siti Hajati Husein (The Juris, 2022)
This study discusses the role of the Notary in carrying out his position in establishing a "relaas" certificate regarding the E-GMS that must be carried out in layers of loyal rules as regulated in Law no. prohibit the 2014 chapter on the Amendment to Law Number 30 of 2004 chapter on Notary Positions and related Financial Services Authority Regulations. This is an advantage to prevent the birth of the onslaught of a Notary in carrying out his position, including helping to submit a legalization of how to multiply his clients. The case that is appointed as part of this analysis is the assistance of a notary in an Electronic General Meeting of Shareholders (E-GMS) in Indonesia following the Law on Notary Positions and the Regulations of the Financial Services Authority and the Legality of the Deed of Relaas part of the Deed of Minutes concerning the General Meeting of Shareholders. Shares held Electronically are listed. The result of part analysis in this analysis is that the Notary in the Implementation of the GMS is domiciled in the establishment of the Deed of the GMS, where the establishment of the poison certificate is carried out without being accustomed to being attended by a Notary. The deed listed can be made part in the form of a Deed of Parties/Deed of Partij with the form of a Statement of Decisions of the General Meeting of Shareholders, or the certificate as well as poison can be made part in the form of an Official Deed/Relaas with the form of Minutes of GMS as part of the GMS section followed by a Notary. With the existence of OJK Regulation Number 16/POJK.04/2020, the GMS can be conducted electronically and the Notary provisions strengthen the E-GMS certificate as part of the Deed of Minutes of the E-GMS Meeting. In addition, the Relaas Deed with the form of the Indigenous E-GMS Minutes of Deed followed the method and involved multiplying the rubber aspect as complicated as justifying the particle of the pledge of the Authentic Deed in advance of Article 1868 of the Civil Code, the GMS which was held electronically, the provisions were stated to be added to the Relaas Deed in the form of the E-GMS Minutes Deed, even though the arrangement was not stated. proficiently and boldly the part in the relevant POJK.